CEGAH HIPERTENSI UNTUK HIDUP LEBIH SEHAT DI RT 09 DUSUN WONOCATUR, KELURAHAN BANGUNTAPAN, KECAMATAN BANGUNTAPAN, KABUPATEN BANTUL - Muchamad Rifai; Muhammad Arfianto; RA. Nurmadella Retno Latifa; Tia Siti Azizah; Bunga Bilbina Rizkika; Erlina Adhia Riyane (LPPM ITB AAS Indonesia Surakarta, 2024)
Hypertension or high blood pressure is a chronic and non-communicable disease that is a global public health problem because of its high prevalence. The target of implementing this activity is the entire community of Rt 09/ Rw 25 Wonocatur Hamlet, Banguntapan Village, Banguntapan District, Bantul Regency, totaling approximately 158 heads of families. From the Community Diagnosis results, it was found that hypertension was the main problem in RT 09 Wonocatur Hamlet. The aim of community service at RT 09 Wonocatur is to provide knowledge and understanding to improve hypertension. The service method is carried out by providing lectures and giving leaflets to the community of RT 09 Wonocatur. The results obtained from community service activities at RT 09 Wonocatur were that there was a change in knowledge which increased among the residents before and after the counseling was carried out.